(τ1, τ2)α-Continuity for Multifunctions. (27th April 2020) - Viriyapong, Chokchai; Boonpok, Chawalit
Abstract : The main goal of this article is to introduce the concepts of upper and lower ( τ 1, τ 2 ) α -continuous multifunctions. Characterizations of upper and lower ( τ 1, τ 2 ) α -continuous multifunctions are investigated. The relationships between upper and lower ( τ 1, τ 2 ) α -continuous multifunctions and the other types of continuity are discussed.